Integration of Al-Quran Values in STEM Learning to Improve Student Achievement in Science Competitions Madrasah at MAS Darul Mursyid Medan - Siregar, Hendra Irwandi; Hasibuan, Silvia Anggraini; Hasibuan, Kholidah Hannum; Siregar, Nur Choiro (KOMUNIKA, 2024)
This study investigates integrating Al-Quran values into STEM (Science, Technology, Engineering, and Mathematics) learning and its impact on student achievement in science competitions at MAS Darul Mursyid Medan. Although many broadly recognize STEM education as fostering critical thinking and problem-solving skills, the challenge lies in merging these technical competencies with moral and ethical development, particularly in religious educational settings. Previous research has focused on the benefits of value-based education. However, people need to understand better how to practically integrate Al-Quran values into STEM and their effect on competitive academic performance. This study addresses this gap by analyzing the relationship between Al-Quran values and student performance. Researchers used a quantitative research design to collect data through structured questionnaires from a purposive sample of 100 students. The data was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. Results indicate a significant positive effect of Al-Quran values on student achievement in science competitions. The high reliability and validity scores reinforce the robustness of the findings. This study has important implications for educators and policymakers, highlighting that integrating religious values into STEM curricula can enhance intellectual and moral development, thus preparing students for academic success and real-world challenges. Future research could explore other religious values in different educational contexts and their influence on broader educational outcomes.